Pengaruh Hutang Jangka Panjang Terhadap Kinerja Perusahaan (Profitabilitas) Di Sektor Industri Makanan Dan Minuman - Effendi, Marwan; Hidayat, Lukman; Sumardimansyah, Ardi (Jurnal Ilmiah Manajemen Kesatuan, 2014)
In the current economic many businesses both large and small businesses in the capital using funds from external sources such as credit or debt. Long-term debt typically arises because of the need for additional funds for the purchase offixed asses; increase the number ofpermanent working capital, buying another company or perhaps to pay of other debs. In managing the profitability of a company that uses long-term debt is planned to determine or establish funds towards investment. The purpose of this study is to determine the results of analyzing the effect of long-term debt on firm perfomance (profitability). The results showed pattially that free variable has no significant effect on the independent variable. The coeficients determination show that there are other variables detennining the returns or profitability. While the establishment of the regression equation sugests that if there is an addition of one-unit on the Longterm Debt Equity the Retum on Equity will decrease. Keywords: long-tem debt, profitability